Os véus de Mira-Celi: sobre a representação da consciência humana na poesia de Jorge de Lima - Signoreli, João Antônio Marra (2018)
It is possible to see throughout the work of Jorge de Lima, especially after what the critic recurrently calls "catholic phase", the presence of the figure of a mystic woman, object of love of the voice that speaks in the poem. This figure is present not only in his book published in Spanish Mira-Coeli and in the Portuguese version Anunciação e Encontro de Mira-Celi, but in every poetic work of Jorge de Lima subsequent to them. The present work aims to investigate what this reference figure, and if it has in it its own reference, what it represents in the field of human experience. For that, it was related to the construction of the work studied, a poetic work, with the accomplishment of a musical work, since music is also a kind of language that has its own reference in itself. In the work, it is stated that this process of signification is a way of representing what, in Aristotelian-Thomist psychology, is called a volitional appetite and it is concluded that the figure of Mira-Celi has the function of stating the purity of will and consciousness in the midst of earthly dramas